Environmental Factor Accelerate the Deterioration of Tuff Stone Heritage: A Case Study of a Stone House in Southeast China - Yang Wu; Jian Shen; Jianchao Zhang; Bingjian Zhang (Buildings, 2022)
Water plays an important role in the deterioration of rocks. Often, the condensation cannot be ignored in addition to the rain and seepage, especially for stone relics built with tuff in humid areas. As part of this study, a century-old stone house in southeastern China was investigated alongside the microclimate, including temperature, humidity, and rainfall in the study area. Results showed that the main types of deterioration in this house were detachment, with some areas exhibiting surface hardness decreased by more than 50%. This decay was caused in part by condensation on the inner walls of the stone house during the rainy season. According to statistics, more than two-thirds of the time the rainy season produces condensate on the inner wall, which is primarily found on the north side of the house because there is less solar radiation. Conversely, the stress caused by severe temperature differences on the south side contributes more to the deterioration of rock. Environmental conditions with high humidity and strong temperature differences will accelerate the deterioration process of tuff stone with high porosity. Consequently, it is recommended that stones built by tuff in such a humid environment take rainproof measures and maintain good air circulation to reduce the adverse effects of condensation.